Possible unconventional superconductivity in substituted BaFe2As2 revealed by magnetic pair-breaking studies - Rosa, P. F. S.; Adriano, C.; Garitezi, T. M.; Piva, M. M.; Mydeen, K.; Grant, T.; Fisk, Z.; Nicklas, M.; Urbano, R. R.; Fernandes, R. M.; Pagliuso, P. G. (Scientific reports, 2014)
The possible existence of a sign-changing gap symmetry in BaFe 2 As 2 -derived superconductors (SC) has been an exciting topic of research in the last few years. To further investigate this subject we combine Electron Spin Resonance (ESR) and pressure-dependent transport measurements to investigate magnetic pair-breaking effects on BaFe 1.9 M 0.1 As 2 ( M = Mn, Co, Cu and Ni) single crystals. An ESR signal, indicative of the presence of localized magnetic moments, is observed only for M = Cu and Mn compounds, which display very low SC transition temperature ( T c ) and no SC, respectively. From the ESR analysis assuming the absence of bottleneck effects, the microscopic parameters are extracted to show that this reduction of T c cannot be accounted by the Abrikosov-Gorkov pair-breaking expression for a sign-preserving gap function. Our results reveal an unconventional spin- and pressure-dependent pair-breaking effect and impose strong constraints on the pairing symmetry of these materials.